Ninety-day perioperative complications of pediatric robotic urological surgery: A multi-institutional study. Issue 2 (April 2016) - Dangle, P.P.; Akhavan, A.; Odeleye, M.; Avery, D.; Lendvay, T.; Koh, C.J.; Elder, J.S.; Noh, P.H.; Bansal, D.; Schulte, M.; MacDonald, J.; Shukla, A.; et al.
Summary: Background: Robotic technology is the newest tool in the armamentarium for minimally invasive surgery. Individual centers have reported on both the outcomes and complications associated with this technology, but the numbers in these studies remain small, and it has been difficult to extrapolate meaningful information. Objectives: The intention was to evaluate a large cohort of pediatric robotic patients through a multi-center database in order to determine the frequency and types of complications associated with robotic surgery for pediatric reconstructive and ablative procedures in the United States. Study design: After institutional review board approvals at the participating centers, data were retrospectively collected (2007–2011) by each institute and entered into a RedCap ® database. Available demographic and complication data that were assigned Clavien grading scores were analyzed. Results: From a cohort of 858 patients (880 RAL procedures), Grade IIIa and Grade IIIb complications were seen in 41 (4.8%); and one patient (0.1%) had a grade IVa complication. Intraoperative visceral injuries secondary to robotic instrument exchange and traction injury were seen in four (0.5%) patients, with subsequent conversion to an open procedure. Grade I and II complications were seen in 59 (6.9%) and 70 (8.2%) patients, respectively; they were all managed conservatively. A total of 14 (1.6%) were converted to an open or pure laparoscopic procedure, of which, 12 (86%) were secondary to mechanical challenges. Discussion: It is believed that this study represents the largest and most comprehensive description of pediatric RAL urological complications to date. The results demonstrate a 4.7% rate of Clavien Grade IIIa and Grade IIIb complications in a total of 880 cases. While small numbers make it difficult to draw conclusions regarding the most complex reconstructive cases (bladder diverticulectomy, bladder neck revision, etc.), the data on the more commonly performed procedures, such as the RAL pyeloplasty and ureteral reimplantation, are robust and more likely represent the true complication rate for these procedures when performed by highly experienced robotic surgeons. Conclusion: Pediatric robotic urologic procedures are technically feasible and safe. The overall 90-day complication rate is similar to reports of laparoscopic and open surgical procedures. Complications: n (%) Life threatening (IVa): 1 (0.1%) Requiring radiologic and or surgical intervention (IIIa and IIIb): 41 (4.8%) Secondary to robotic system: 4 (0.5%) Mechanical failure leading to conversion: 14 (1.6%)